Oral Health-Related Quality of Life of Hong Kong Kindergarten Children Receiving Silver Diamine Fluoride Therapy - Hollis Haotian Chai; Ivy Guofang Sun; Duangporn Duangthip; Sherry Shiqian Gao; Edward Chin Man Lo; Chun Hung Chu (MDPI AG, 2024)
The objective of this prospective 12-month observational study is to examine the oral health-related quality of life (OHRQoL) among Hong Kong young children aged 3-4 years old receiving silver diamine fluoride (SDF) therapy for carious upper anterior primary teeth. A parental questionnaire was used to collect each child's sociodemographic background and oral health habits at baseline. Data on parents' satisfaction with their child's dental aesthetics were collected at baseline and during a 12-month visit. The Chinese Early Childhood Oral Health Impact Scale (C-ECOHIS) was used to measure OHRQoL. A trained dentist performed examinations and recorded caries experience (dmft) and oral hygiene (visible plaque index) at baseline and 12 months. SDF was applied to the carious lesions. Out of 286 invited children, 248 (87%, 248/286) participated, and 211 (85%, 211/248) attended the 12-month examination. All SDF-treated carious lesions were discoloured at the 12-month examination. Regression analysis showed that the baseline C-ECOHIS score was associated with dmft (p < 0.001). The baseline and 12-month C-ECOHIS scores were 4.6 ± 5.5 and 5.0 ± 5.6, respectively (p = 0.42). The scores for parental satisfaction with dental aesthetics at baseline and 12 months were 59% to 46% (p < 0.001). Satisfaction was negatively associated with the number of discoloured upper anterior teeth (p < 0.001). In conclusion, SDF discoloured the carious upper anterior teeth of the Hong Kong kindergarten children. However, the discoloured lesions had no significant effects on the OHRQoL of these children. However, more parents became dissatisfied with their child's dental aesthetics after SDF therapy. Hence, clinicians should inform parents well before they perform SDF therapy on children.